FAT-FREE MASS INDEX AND FAT MASS INDEX OF INHABITANTS OF THE CITY OF BIALA PODLASKA - Agnieszka Wasiluk; Jerzy Saczuk (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Introduction: A steady and considerable increase in the incidence of overweight and obesity is observed in the majority of developed countries. It affects every age group, regardless of sex and race. One of the causes of this negative trend, which has already reached an epidemic scale, is negative changes in lifestyle. We spend increasingly more time in front of a TV or a computer screen at the expense of other activities requiring energy expenditure. Purpose: The aim of this study was to analyze changes in body components of adult inhabitants of Biala Podlaska and determine the reference values for FFMI and FMI. Materials and method: The examined 668 women and 674 men (20 years old and older) inhabitants of Biala Podlaska. Values of somatic traits were evaluated on the basis of anthropometric measurements. Tissue composition was evaluated with the bioelectrical impedance method. Results: The reference values of FMI (25th-75th centile) in women ranged from 7.15 kg/m 2 to 12.93 kg/m 2, whereas in men from 4.94 kg/m 2 to 9.43 kg/m 2. In women the reference values FFMI ranged from 15.29 kg/m 2 to17.28 kg/m 2 and were similar in all calendar age groups. The reference values for all men ranged between 18.76 kg/m 2 and 22.01 kg/m 2 and were the lowest in the oldest category of age. Conclusions: The data presented in the following study might be useful for physicians and nutritionists as control values.